Efficacy and safety of fluorescence navigation combined with 3D imaging in precise liver resection: A systematic review and meta-analysis - Chunwei Xu; Xinhua Cui; Jiafei Che; Xiaojing Shen; Dingchao Chen (Photodiagnosis and Photodynamic Therapy)
Objective: This study aimed to evaluate the effectiveness and safety of fluorescence navigation combined with three-dimensional imaging (FN&3DI) technology in precise liver resection. Methods: A systematic search was conducted in the PubMed, Web of Science, Embase, and Cochrane Library databases for all English-language publications on fluorescence-guided navigation combined with three-dimensional (3D) imaging technology–assisted precise liver resection, with a cutoff date of July 2024. After assessing the quality of the included studies and extracting relevant data, a meta-analysis was performed using Stata 12.0 software. Results: A total of 6 studies involving 451 patients were included in this study, with 207 patients in the FN&3DI group and 244 patients in the conventional surgery (CS) group. The meta-analysis results showed that the FN&3DI group exhibited significantly lower values than the CS group in terms of intraoperative blood loss [mean difference (MD) = –97.90, 95 % confidence intervals (CI) = –151.15 to –44.66, P = 0.000], intraoperative blood transfusion rates [odds ratios (OR) = 2.96, 95 % CI = 1.71–5.10, P = 0.000], hospital stay (MD = –0.91, 95 % CI = –1.78 to –0.04, P = 0.041), and overall postoperative complications (OR = 1.68, 95 % CI = 1.11 to 2.53, P = 0.014). However, the FN&3DI group exhibited significantly longer surgery time (MD = 57.36, 95 % CI = 13.31–101.40, P = 0.011), but no statistically significant difference was noted in conversion rate, R0 resection margins, and postoperative recurrence between the two groups. Conclusion: Fluorescence navigation combined with 3D imaging technology is safe and feasible for guiding precise liver resection.